Prevalence of iron deficiency in first trimester, nonanemic pregnant women. (19th March 2021) - Auerbach, Michael; Abernathy, Jessica; Juul, Sandra; Short, Vanessa; Derman, Richard
Abstract: Despite a high frequency of iron deficiency in pregnancy, the United States Preventative Services Task Force (USPSTF) stated: "there is inconclusive evidence routine supplementation for iron deficiency anemia improves maternal or infant clinical health outcomes." In contradistinction, high-quality epidemiologic studies report long lasting deficits in infants diagnosed with iron deficiency in the first 6 months of life compared with infants who were not, with specific deficits in cognition, memory, executive function and electrophysiology documented up to 19 years of age. Infants are not routinely screened for iron deficiency. United Kingdom guidelines differ and recommend screening high-risk infants who are preterm, of diabetic, underweight, obese, or vegetarian mothers, those born to anemic or iron deficient mothers, of smokers, those with inflammatory bowel disease or abnormal uterine bleeding, and from pregnancies in which the intergravid period is <6 months. Iron parameters are not routinely drawn unless anemia is present and in some cases only if microcytic. In that iron deficiency precedes the development of anemia, and waiting for its development misses a large number of overtly iron deficient gravidas. Iron parameters were measured in 102 consecutive, nonselected, nonanemic, first trimester women presenting to their obstetricians. Using standard cutoffs of percent transferrin saturation and/or serum ferritin, 42% were observed to be iron deficient. Given the lack of harm of testing for iron deficiency, it appears prudent to err on the side of caution and screen all presenting pregnant mothers until properly powered outcome data become available. The current recommendations of the USPSTF may need to be revisited.